Penerapan Model Pembelajaran PBL Berbantu Media TTS dalam Meningkatkan Hasil Belajar Biologi Siswa Kelas X - Paramita Pratiwi; Nurkholisah N; Winda Anista; Agus Prasetyo Utomo (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
This study aims to improve the biology learning outcomes of class X IPA 6 SMAN 1 Glagah. This is interesting to study because the learning process has not varied so that students are less participatory and more easily bored so that it affects learning outcomes. This study used classroom action research which consisted of two cycles. research subjects amounted to 35 students. After the action was taken using the PBL learning model assisted by crossword media, it was found that the percentage of students' completeness had increased. The percentage of students' completeness during the pre-action was 40%, then in the first cycle the percentage of completeness increased to 57.1% and in the second cycle to 77.1%. Based on these data, it can be concluded that the crossword puzzle media can improve the learning outcomes of class X IPA 6 SMAN 1 Glagah in biology lessons.